The order and vsage of the keeping of a parlement in England, and The description of tholde and ancient cittie of Fxcester [sic]. Collected by Iohn Vovvel alias Hooker gentleman - Hooker, John 1526?-1601 (Early English Books Online / EEBO, 1575)
eebo-0113